Machine learning methods for performance forecast and assessment of female handball players - Narendra, M.; Rayudu, K. M.; Sivaratna Sai, T.; Anitha, P.; Lakshmi Parvathi, A. (Mathematical Statistician and Engineering Applications, 2022)
System learning algorithms are used to carry out tasks that people find difficult to do. The evaluation and forecasting of the performance of precise fitness sports using players as a resource is becoming more and more important in both league and practice scheduling. When it becomes Due to the use of conventional methods, the variety and difficulty of particular sorts of sporting events, and the usually time-variant interactions among them, sports are difficult to research and predict. Strong Machine Learning (ML) algorithms can analyse gamers' physical requirements with remarkable accuracy.